5-nitro-2-furaldehyde N-(hydroxymethyl)-semicarbazone - Doriguetto, A. C.; Silva, CHTD; Ellena, J.; Trossini, GHG; Chin, Chung Man [UNESP]; Ferreira, E. I. (Blackwell Publishing, 2005)
The title compound, C7H8N4O5, which is a potential anti-Chagas' derivative, was synthesized using a simple hydroxymethylation method in a basic medium with formaldehyde. The structure reveals two infinite two-dimensional networks in the ( 102) and ( 001) planes, stabilized by intermolecular hydrogen bonds.